2005
DOI: 10.1051/lait:2005008
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of front-face fluorescence spectroscopy to determine the geographic origin of milks from the Haute-Loire department (France)

Abstract: -A total of 40 milk samples, i.e., 8 milks produced in lowland (430-480 m), 16 milks produced in mid-mountain (720-860 m) and 16 milks produced in mountain (1070-1150 m) areas of the Haute-Loire department (France), sampled at key periods of animals feeding, were analysed by front-face fluorescence spectroscopy. Tryptophan, aromatic amino acids and nucleic acid (AAA+NA) and riboflavin fluorescence spectra were recorded in triplicate on different aliquots directly on milks with the excitation wavelengths set at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 30 publications
(50 reference statements)
2
36
2
Order By: Relevance
“…Regarding the prediction of the pH value, the results obtained in the present study were less successful than those obtained by Karoui et al [16] on 15 different soft cheeses. Indeed, the authors pointed out that the determination of the pH value by fluorescence techniques could be considered as approximate, while in the present study an unsuccessful result was obtained.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the prediction of the pH value, the results obtained in the present study were less successful than those obtained by Karoui et al [16] on 15 different soft cheeses. Indeed, the authors pointed out that the determination of the pH value by fluorescence techniques could be considered as approximate, while in the present study an unsuccessful result was obtained.…”
contrasting
confidence: 99%
“…Concerning the prediction of TP, similar results to those observed with the investigation of Karoui et al [16] was found, while the poorest results were obtained in the present study for SP compared with those observed by Karoui et al [16] on 15 different soft cheeses. Again, this could Predicted dry matter (g .…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, Wold et al [49] have reported that fluorescence properties of riboflavin can be used to measure the degree of degradation of this molecule in dairy products. Finally, front-face spectroscopy has been utilised to determine the geographic origin of milk [28], PDO Gruyère and L'Etivaz PDO cheeses [15,26] and Emmental cheeses from different European geographic origins, manufactured during winter and summer periods [24,25,27].…”
Section: Introductionmentioning
confidence: 99%